2014
DOI: 10.1111/echo.12503
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease is Independently Associated with Alterations in Left Atrial Function

Abstract: Left atrial dysfunction is evident in stage 3 CKD with associated LA enlargement. This study demonstrates that LA GS and SR were reduced in the CKD group despite similar LAVI in the CKD with HT and HT group. Hence LA GS and SR may be a more sensitive noninvasive tool to detect cardiovascular involvement in CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…In a study comparing stage 3 CKD patients to age and risk factor matched controls as well as healthy controls, Kadappu et al reported PALS to be reduced in both CKD group and hypertensive control group compared to healthy controls, with a significant difference among the three groups, pointing to an independent and incremental effect of CKD on LA function (28). These findings were further corroborated in a larger study involving 228 participants whereby PALS and ASr were noted to be significantly altered in the CKD group, with LA strain being the most sensitive parameter of myocardial involvement with alterations in LA strain proceeding changes to LA volume (66). Similar findings were demonstrated by Ohara et al in their study investigating LA function in CKD patients with normal LA size; LA strain was impaired in CKD patients despite normal LA size, and in comparison to the control group (68).…”
Section: Chronic Kidney Disease (Ckd)mentioning
confidence: 60%
See 1 more Smart Citation
“…In a study comparing stage 3 CKD patients to age and risk factor matched controls as well as healthy controls, Kadappu et al reported PALS to be reduced in both CKD group and hypertensive control group compared to healthy controls, with a significant difference among the three groups, pointing to an independent and incremental effect of CKD on LA function (28). These findings were further corroborated in a larger study involving 228 participants whereby PALS and ASr were noted to be significantly altered in the CKD group, with LA strain being the most sensitive parameter of myocardial involvement with alterations in LA strain proceeding changes to LA volume (66). Similar findings were demonstrated by Ohara et al in their study investigating LA function in CKD patients with normal LA size; LA strain was impaired in CKD patients despite normal LA size, and in comparison to the control group (68).…”
Section: Chronic Kidney Disease (Ckd)mentioning
confidence: 60%
“…The cause for LA changes are multifactorial and have traditionally correlated with presence of LV hypertrophy, degree of diastolic dysfunction as well as common coexisting cardiovascular risk factors such as hypertension and diabetes mellitus (65)(66)(67).…”
Section: Chronic Kidney Disease (Ckd)mentioning
confidence: 99%
“…Sudden cardiac death in patients with chronic renal failure is associated with increased levels of inflammatory markers such as high-sensitivity C-reactive protein and interleukin 6 which are both linked to fibrotic changes of the myocardium and the electrical conduction system itself [19]. Previous studies reported that chronic kidney disease is independently associated with alterations in left atrial function (left atrial volume and atrial strain rate) as well as ventricular strain rates, both markers for myocardial fibrosis [20,21].…”
Section: Chronic Renal Failurementioning
confidence: 99%
“…Combination of LV diastolic dysfunction and left atrial dysfunction is associated with quantitative left atrial remodeling in patients with diabetes [40].…”
Section: Diabetesmentioning
confidence: 99%